2019
DOI: 10.1177/0040517519844215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of harvesting and ginning practices on Southern High Plains cotton: fiber quality

Abstract: The lint yield and fiber quality of cotton produced in the Southern High Plains of the USA have improved over the last decade, renewing interest in finding harvest and ginning practices that better preserve fiber quality. Previous research showed that picker harvesting and roller ginning may better preserve fiber quality, but conventional roller ginning was too slow to be adopted as the primary ginning system used for Upland cotton. Advancements in roller ginning technology have increased the ginning rate per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Once picked from the farm cotton is further processed in gins to separate fiber, leaving behind cotton gin trash (CGT) as agro-industrial waste. According to Thomasson [15], ginning one bale (217-218 kg) of cotton yields about 37-147 kg of CGT [16], thus annually generating millions of tons of CGT in the states of Texas, Georgia, Arkansas, and Mississippi. The CGT, a byproduct of the cotton industry, mainly composed of clean lint (8-15%), hulls (18.5-32.9), stem (5.2-5.9), grass (0.1-1.1), seed (0-2.9%), motes (20.4-21.6%), small leaves (19.4-34.9%) [17] is abundantly available in cotton-growing regions of the US.…”
Section: Introductionmentioning
confidence: 99%
“…Once picked from the farm cotton is further processed in gins to separate fiber, leaving behind cotton gin trash (CGT) as agro-industrial waste. According to Thomasson [15], ginning one bale (217-218 kg) of cotton yields about 37-147 kg of CGT [16], thus annually generating millions of tons of CGT in the states of Texas, Georgia, Arkansas, and Mississippi. The CGT, a byproduct of the cotton industry, mainly composed of clean lint (8-15%), hulls (18.5-32.9), stem (5.2-5.9), grass (0.1-1.1), seed (0-2.9%), motes (20.4-21.6%), small leaves (19.4-34.9%) [17] is abundantly available in cotton-growing regions of the US.…”
Section: Introductionmentioning
confidence: 99%
“…The complete harvesting and ginning treatment structure for each year and cultivar is shown in Table 1. A detailed study of the fiber quality aspects of these cottons was reported by Wanjura et al 18 Ginned lint was transported to the USDA Cotton Structure and Quality Research Unit in New Orleans, LA, for fiber quality testing and textile processing. The quantity of lint produced from each of the 80 field lots was insufficient to carry out the intended textile processing trials, as at least 50 kg of fiber was needed for the production of all three yarn types.…”
Section: Methodsmentioning
confidence: 99%
“…More explicitly, various processes in the garments manufacturing industry e.g. selection of raw material ( Amindoust and Saghafinia, 2017 ; Avadí et al., 2020 ; Daksa Ejeta et al., 2020 ), suppliers ( Daksa Ejeta et al., 2020 ; Morali et al., 2016 ; Sela et al., 2020 ), cotton harvesting ( Afzal et al., 2020 ; Sluijs and Roth, 2020 ; Wanjura et al., 2019 ), spinning ( Fockink et al., 2020 ; Shao and Ma, 2019 ; Singh and Kumar, 2019 ), weaving ( Baydar et al., 2015 ; El-Gohary et al., 2013 ; Hossain et al., 2018 ), dry and wet processing ( Alkaya and Demirer, 2015 ; Fresner, 1998b ; Kiran-Ciliz, 2003 ; Zhang et al., 2016 ), washing ( Dumitrescu et al., 2008 ; Maryan and Montazer, 2013 ), bleaching ( Baban et al., 2010 ; Narayanaswamy and Scott, 2001 ), dyeing ( Al-Yousfi, 2004 ; Bhuiyan et al., 2018 ; Chen et al., 2017 ; Gong et al., 2018 ; Haji and Naebe, 2020 ; Long et al., 2014 ; Ozturk et al., 2015 , 2014 ; Pisitsak et al., 2018 ; Schramm, 1998 ; Silva et al., 2018 ; Xiao et al., 2017 ; Yukseler et al., 2017 ), printing ( Chen and Long, 2018 ; Ibrahim et al., 2015 ; C. Li et al., 2018 ; Tong et al., 2012 ), treatment of emissions/waste-water ( Ali et al., 2016 ; Liang et al., 2018 ) and packaging/finishing processes ( Ali et al., 2016 ; Benli and Bahtiyari, 2015 ; Manring and Moore, 2006 ; Ozturk et al., 2016 ) can be positively abridged and streamlined with the implementation of CPP at company level ( Alkaya and Demirer, 2015 ; de Oliveira et al....…”
Section: Literature Reviewmentioning
confidence: 99%